Uncovering changing prescriptions and practices around organic agriculture in Metro Manila, the Philippines. Issue 5 (28th May 2017) - Sahakian, Marlyne; Leuzinger, Tiphaine; Saloma, Czarina
ABSTRACT: Through the lens of social practice theories, we consider the emergence of organic food in the Philippines and relate this to sustainable food production and consumption. In particular, we analyze the various practices of groups engaged in "organic" food production and consumption in the capital region, Metro Manila—in a country that has a vibrant organic agriculture movement and which has recently introduced a national law promoting organic food. Using qualitative data, we assess the development of new prescriptions or guidelines and the tensions that arise between prescriptions and public policies. We argue that, as people take on new competencies and meanings in relation to organic produce, social inequalities among consumers are highlighted, affecting the trajectories of organic food.